2021
DOI: 10.3389/fspor.2021.634258
|View full text |Cite|
|
Sign up to set email alerts
|

Fatigue-Related Changes in Spatiotemporal Parameters, Joint Kinematics and Leg Stiffness in Expert Runners During a Middle-Distance Run

Abstract: Fatigue with its underlying mechanisms and effects is a broadly discussed topic and an important phenomenon, particularly in endurance sports. Although several studies have already shown a variety of changes in running kinematics with fatigue, few of them have analyzed competitive runners and even fewer have focused on middle-distance running. Furthermore, the studies investigating fatigue-related changes have mostly reported the results in terms of discrete parameters [e.g., range of motion (RoM)] in the fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
1
16
1
Order By: Relevance
“…Recently, it has been shown that running-induced fatigue does not affect the spatiotemporal parameters or their variability in novice runners, although the position of the CoM is affected [ 20 ]. This is in contrast to findings in expert runners, which have shown that a high-intensity run with a similar time to exhaustion affects the spatiotemporal parameters and their variabilities [ 21 ]. The changes in the CoM position that occur with the fatigue seen in novice runners (a lower position around the heel strike and an increased range of motion (RoM) in the medio-lateral direction) might be explained by a loss of control of the CoM.…”
Section: Introductioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Recently, it has been shown that running-induced fatigue does not affect the spatiotemporal parameters or their variability in novice runners, although the position of the CoM is affected [ 20 ]. This is in contrast to findings in expert runners, which have shown that a high-intensity run with a similar time to exhaustion affects the spatiotemporal parameters and their variabilities [ 21 ]. The changes in the CoM position that occur with the fatigue seen in novice runners (a lower position around the heel strike and an increased range of motion (RoM) in the medio-lateral direction) might be explained by a loss of control of the CoM.…”
Section: Introductioncontrasting
confidence: 89%
“…A multitude of parameters regarding efficiency, injury prevention and performance could also be of interest, as these are important during running and should therefore be stabilized or held constant. (4) When calculating the SPM over the whole gait cycle, an error might occur because the ratio between the stance- and swing-phase durations might change with fatigue [ 21 ]. However, in our previous study, we found no changes in the spatiotemporal parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Novice runners showed an increase in trunk forward lean which was not seen in expert runners and an increase in hip abduction during mid-swing, whereas a decrease was found for expert runners. This indicates that fatigue effects found in expert runners [15,16] are not directly transferable to novice runners. In experienced runners, effects of fatigue on spatiotemporal and stiffness parameters [15,17], on joint kinematics and kinetics [18] and on leg symmetry [19] were found.…”
Section: Introductionmentioning
confidence: 91%
“…A previous study found that the runner hip, knee, and ankle joint ROM in the sagittal plane during the stance phase increased with fatigue at a xed speed. The runner maintained the balance of mechanical torque and angular displacement to produce the same level of mechanical power during the running period, while the reduction in joint torque or muscle force caused by the increase in exercise time induced an increase in joint ROM [22]. Therefore, the right/left hip average ROM increased over time, which may be due to a stable strategy adopted by the runner throughout the exercise time to maintain a constant running speed in the entire exercise time.…”
Section: Changes In Average Rommentioning
confidence: 99%